PERENCANAAN SISTEM PENGKONDISIAN UDARA ZONA 1 GEDUNG B RUMAH SAKIT UNIVERSITAS BENGKULU OLEH PT DETA DECON - Hernan Marten Karosekali; Putra Bismantolo; Sunggoro (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2026)
This study discusses the planning of an air conditioning system in Zone 1 Building B of Bengkulu University Hospital. The planning of an Heating, Ventilation, and Air Conditioning (HVAC) system in hospitals is crucial because it is closely related to thermal comfort, which is defined as the condition in which the human body does not feel too hot or too cold, allowing metabolism and activities to function optimally. In the hospital context, thermal comfort is not only important for patient convenience but also plays a role in supporting recovery processes, maintaining air quality, and ensuring a hygienic environment in accordance with health standards. The aim of this study is to calculate the cooling load using the ASHRAE method and compare it with simulation results, as well as to evaluate whether the installed cooling capacity meets the actual requirements. The results show that the total cooling load based on the ASHRAE method is 163,142.17 BTU/h, while the simulation application produces 174,225 BTU/h. The installed cooling capacity is 191,900 BTU/h, which indicates that the system is sufficient with a slight oversizing. This oversizing provides a safety margin but may lead to higher energy consumption if not properly controlled. These findings highlight that proper HVAC planning is essential to ensure comfort, energy efficiency, and compliance with technical regulations in hospital buildings.